Evaluation of modified interventions of integrated Traditional Chinese and western medicine in nursing of stroke patients (中风患者中西医结合优化护理干预效果观察) - LI Yanmin (李艳敏); HUANG Chaoping (黄朝萍) (中西医结合护理)
Objective To analyze the clinical effect of modified interventions of integrated Traditional Chinese and western medicine in nursing of stroke patients. Methods A total of 78 stroke patients were randomly divided into the control group and observation group, with 39 cases in each group. All patients received routine nursing interventions in the rehabilitation training, and those in the observation group were given modified interventions of integrated Traditional Chinese and western medicine. The Activity of Daily Living (ADL) and Fugl-Meyer Assessment (FMA) scores were compared between two groups, and patients’ satisfaction with nursing service was evaluated by using self-made questionnaire. Results Scores of ADL and FMA were increased in both two groups after interventions, and Scores of ADL and FMA in the observation group were higher than those in the control group (P＜0. 05). The nursing satisfaction rate of the observation group was higher than that of the control group, with a significant difference (P＜0. 05). Conclusion Modified interventions of integrated Traditional Chinese and western medicine are effective to improve the rehabilitation of limb motor function after stroke, and improve the prognosis and quality of life of stroke patients. (目的 分析对中风患者实施中西医结合优化护理干预的效果。方法 选取医院神经内科2018年4月—2019年4月收治的中风患者78例为研究对象, 随机分为对照组和观察组, 各39例。对照组患者康复训练中运用常规护理模式, 观察组在对照组基础上增加中西医结合优化护理干预。对比两组患者的生活质量评分和肢体运动功能评分, 采用自制量表评价患者护理满意度。结果 干预后, 观察组患者生活活动能力量表(ADL)评分和Fugl-Meyer评定量评分高于对照组, 差异有统计学意义(P＜0. 05)。观察组护理满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 对中风患者实施中西医结合优化护理干预措施, 能够促进患者运动功能康复, 对改善预后和生活质量具有积极意义。)